Review of Barrio Libre (AmeriQuests, 2017)
Review of: Barrio Libre: Criminalizing States and Delinquent Refusals of the New Frontier by Gilberto Rosas. Durham, NC, Duke UP, 2012. p. xi, 200. Notes. Bibliography. Index. $23.95 paper